Lowered nutritional quality of plankton caused by global environmental changes - Lau, Danny C P; Jonsson, Anders; Isles, Peter D. F.; Creed, Irena F.; Bergström, Ann-Kristin (2021)
Global environmental changes are causing widespread nutrient depletion, declines in the ratio of dissolved inorganic nitrogen (N) to total phosphorus (DIN:TP), and increases in both water temperature and terrestrial colored dissolved organic carbon (DOC) concentration (browning) in high-latitude northern lakes. Declining lake DIN:TP, warming, and browning alter the nutrient limitation regime and biomass of phytoplankton, but how these stressors together affect the nutritional quality in terms of polyunsaturated fatty acid (PUFA) contents of the pelagic food web components remains unknown. We assessed the fatty acid compositions of seston and zooplankton in 33 lakes across south-to-north and boreal-to-subarctic gradients in Sweden. Data showed higher lake DIN:TP in the south than in the north, and that boreal lakes were warmer and browner than subarctic lakes. Lake DIN:TP strongly affected the PUFA contents-especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)-in seston, calanoids, and copepods (as a group), but not in cladocerans. The EPA+DHA contents increased by 123% in seston, 197% in calanoids, and 230% in copepods across a lake molar DIN:TP gradient from 0.17 to 14.53, indicating lower seston and copepod nutritional quality in the more N-limited lakes (those with lower DIN:TP). Water temperature affected EPA+DHA contents of zooplankton, especially cladocerans, but not seston. Cladoceran EPA+DHA contents were reduced by ca. 6% for every 1 degrees C increase in surface water. Also, the EPA, DHA, or EPA+DHA contents of Bosmina, cyclopoids, and copepods increased in lakes with higher DOC concentrations or aromaticity. Our findings indicate that zooplankton food quality for higher consumers will decrease with warming alone (for cladocerans) or in combination with declining lake DIN:TP (for copepods), but impacts of these stressors are moderated by lake browning. Global environmental changes that drive northern lakes toward more N-limited, warmer, and browner conditions will reduce PUFA ...